Global stroke burden attributable to household air pollution: Insights from GBD 2021 and projections to 2040 - Manqing Li; Shicheng Liao; Chao Wang; Haojia Ma; Xiumei Xing; Jianhui Yuan; Jie Jiang; Zhuoying Zeng (PLoS ONE, 2025)
Objectives To analyze the global stroke burden attributable to household air pollution (HAP) using Global Burden of Disease (GBD) 2021 data, examine its spatiotemporal patterns from 1990–2021, and project future trends through 2040. Study design Retrospective analysis using GBD data with future projections Methods Analysis of age-standardized rates, deaths, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) due to HAP-related stroke across 204 countries. The linear regression model examined global time trends. Cluster analysis investigated the patterns of disease burden changes across GBD regions. The Nordpred model projected trends up to 2040. Results In 2021, HAP caused 1.23 million stroke deaths and 26.78 million DALYs globally. From 1990–2021, age-standardized death rates (EAPC = −0.37), DALY rates (EAPC = −0.20), and YLL rates (EAPC = −0.30) decreased, while YLD rates increased (EAPC = 1.11). Males showed a higher burden than females, with peak rates in the 80–84 age group. Middle-SDI regions had the highest age-standardized rates, with East Asia recording the largest absolute numbers. South and East Asia showed significant increases, while Western Europe, Eastern Europe, and High-income North America showed the greatest declines. Predictions using the Nordpred model indicated rising absolute numbers of deaths (to 1.79 million), DALYs (to 34.76 million), YLDs (to 3.29 million), and YLLs (to 31.39 million), with males consistently bearing a higher burden, though ASRs are expected to decline for both sexes. Conclusions Our findings suggest that regions with higher economic development and greater adoption of clean energy are associated with lower HAP-related stroke burden, possibly through improvements in indoor air quality. The observed regional and gender disparities emphasize the need for targeted interventions, particularly in less developed regions and among high-risk groups such as men and older adults.